Application of the Demonstration Learning Model to Improve Student Learning Outcomes on Basic Competencies in Drawing Letters, Numbers and Etiquette in Technical Drawing at SMK Negeri 1 Hiliserangkai for the 2022/2023 Academic Year - Arman Jaya Gulo; Adrianus Zega; Yelisman Zebua (CV. Rayyan Dwi Bharata, 2023)
The problem in this study is that the implementation of the Demonstration learning model has not been implemented optimally so that student learning outcomes in the basic competencies of Drawing Letters, Numbers and Etiquette are only limited to meeting the KKM standard that has been set, namely 70. The purpose of this study: (1) To describe the implementation of the learning process by apply the Demonstration learning model. (2) To find out the increase in student learning outcomes in the basic competencies of Drawing Letters, Numbers and Etiquette in technical drawings at SMK Negeri 1 Hiliserangkai. This type of research is Classroom Action Research (CAR). This research was conducted at SMK Negeri 1 Hiliserangkai with the research subjects being students of class X-BKP Semester I for the 2022/2023 academic year with a total of 18 students. The research instrument (1) Observation Sheet, consisting of (a) Observation sheet observing the learning process for teachers (b) Observation sheet observing students in the learning process. (2) Student Learning Outcomes Test and (3) Photo documentation. Research Results: (1) In Cycle I (first) the average learning process (teacher respondents) was 67.04%, and the average percentage of observations of students' activeness in the learning process was 47.40% had not reached the target set, the average -the average student learning outcomes is 67.89% belonging to the sufficient category, the percentage of student learning completeness is 66.67%. (2) In Cycle II (two) the average learning process (teacher respondents) is 92.04% and the average percentage of observations of student activity in the learning process is 81.77% has reached the set target, the average learning outcomes students namely 89.22% belonging to the good category, the percentage of completeness of students namely 100% has reached the set target of 70%. From the results of the research findings above, it can be concluded that by applying the Demonstration learning model to the Basic Competence of Drawing Letters, Numbers and Etiquette in Technical Drawings, it can improve student learning outcomes for class X-BKP SMK Negeri 1 Hiliserangkai for the 2022/2023 Academic Year.